REST from research to practice - Wilde, Erik 1967-; Pautasso, Cesare (Springer, 2011)
oring ways of developing and implementing applications for REST, the Representational State Transfer system architecture conceived along with the World Wide Web, is gaining prominence as a research topic in academia and industry. Edited by two of the leading lights in REST research, this volume features edited and expanded papers from a key workshop at the 2010 World Wide Web conference, as well as further contributions by researchers on the cutting edge of REST development. The chapters aim to build understanding between those engaged in the abstractions of academic research on REST and the many originators and designers of processes claiming to be RESTful. As well as covering the core principles of REST's architectural style, this significant contribution to the literature on Web development examines a number of REST applications that appear to display advantages over its competing WS architecture. Contributors also assess the benefits REST brings to pervasive computing and cast an eye towards the future with a section on open research questions such as deciding on resource granularity, modeling metadata, and handling transactions.